UTILITY 1 SERVER ON QUEUE SERVICE (STUDY: BANK ACCOUNT NUMBER CONVERSION) - Johan Alfian Pradana (Airlangga Journal of Innovation Management, 2021)
Fast-paced, precise demands and time minimization are dominant to support the service business. Service activities are always expected to be the best by customers. Especially ABC bank customers. Since the information about account conversion, many customers have come to the Bank. The server utility of the queue system plays an important role. One of them is about measuring the usefulness of the queue system, average expectations of waiting times, and expectations of the number of customers in the system. Services that focus on providing services always experience long lines. Therefore, the queue theory is used to assess utilities, waiting for time expectations, and expectations of customer numbers. Research methods using system performance. First, calculate the value of the speed, average service, service level, and performance of the queue system. The result is a queue system of 1 server on average - working with a utility value of 83.5% and the highest in the 4th week, with an average expectation - average waiting time of 0.428 or 25.6 minutes and an expectation of the number of customers in the system of 4.8 or 5 customers. The role of 1 server has not been practical to minimize waiting time expectations.